Single Photon Emission Tomography Imaging in Parkinsonian Disorders: A Review - Paul D. Acton; P. David Mozley (Behavioural Neurology)
Parkinsonian symptoms are associated with a number of neurodegenerative disorders, such as Parkinson’s disease, multiple system atrophy and progressive supranuclear palsy. Pathological evidence has shown clearly that these disorders are associated with a loss of neurons, particularly in the nigrostriatal dopaminergic pathway. Positron emission tomography (PET) and single photon emission tomography (SPECT) now are able to visualise and quantify changes in cerebral blood flow, glucose metabolism, and dopaminergic function produced by parkinsonian disorders. Both PET and SPECT have become important tools in the differential diagnosis of these diseases, and may have sufficient sensitivity to detect neuronal changes before the onset of clinical symptoms. Imaging is now being utilised to elucidate the genetic contribution to Parkinson’s disease, and in longitudinal studies to assess the efficacy and mode of action of neuroprotective drug and surgical treatments. This review summarises recent applications of SPECT imaging in the study of parkinsonian disorders, with particular reference to the increasing role it is playing in the understanding, diagnosis and management of these diseases.